2015
DOI: 10.5009/gnl14039
|View full text |Cite
|
Sign up to set email alerts
|

Screening Colonoscopy among Uninsured and Underinsured Urban Minorities

Abstract: Background/AimsUninsured individuals have lower rates of screening colonoscopy (SC), and little is known regarding the pathology results obtained when they undergo colonoscopies. Since 2004, we have participated in a program that offers SC to uninsured New Yorkers; herein, we report our findings.MethodsUninsured, average-risk patients who were at least 50 years of age underwent SC at our institution between April 2004 and June 2011. We analyzed polyp pathology, location, size, incidence of adenomas, and incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…In a study of uninsured individuals visiting community health clinics in NYC, Collazo et al 47 found a significant difference in polyp detection across race/ethnicity, but did not find statistically significant differences in polyp type, location or advanced pathology across groups. Similarly, Lane et al 46 did not find statistically significant differences in risk of having an adenoma between African American and White uninsured patients from Suffolk County, NY.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study of uninsured individuals visiting community health clinics in NYC, Collazo et al 47 found a significant difference in polyp detection across race/ethnicity, but did not find statistically significant differences in polyp type, location or advanced pathology across groups. Similarly, Lane et al 46 did not find statistically significant differences in risk of having an adenoma between African American and White uninsured patients from Suffolk County, NY.…”
Section: Discussionmentioning
confidence: 96%
“…Others have reported increased CRC screening rates in uninsured and underserved populations in similar programs using patient navigation. 33,[42][43][44][45][46][47] In a study of primarily uninsured patients from Suffolk County, New York, Lane et al 46 found that providing 800 FQHC patients with direct access to colonoscopy resulted in a 37% PDR, a 26% ADR, a 3% no-show rate, a 95%-99% cecal intubation rate, and a 92% good-to-excellent bowel preparation rate. Wolf et al 44 implemented a statewide colonoscopy screening program including 13,000 uninsured Colorado residents, and reported a 93% adequate bowel preparation rate, a 97% cecal intubation rate, and a 28% ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors such as health literacy (8), risk perception (9), lack of health insurance (10) and social influence (11) are associated with cancer screening rates. However, provider-patient communication regarding screening tests may play one of the strongest modifiable roles in cancer screening behavior (12).…”
Section: Introductionmentioning
confidence: 99%
“…We collected the colonoscopy and pathology results of each participant from the electronic medical record, similar to our approach in previous studies [18, 23]. Expert board-certified GI pathologists at The Mount Sinai Hospital analyzed the original pathology specimens.…”
Section: Methodsmentioning
confidence: 99%
“…For the past seven years, our group has conducted prospective studies to help eliminate disparities in CRC screening by facilitating SC among minority populations, including Latinos, served by our institution [4, 18, 23]. These studies have involved an open-access referral system and patient navigation (PN) [26].…”
Section: Introductionmentioning
confidence: 99%